After the fall: Responding to the Champlain Towers building collapse - Beidel, Deborah C.; Rozek, David C.; Bowers, Clint A.; Newins, Amie R.; Steigerwald, Victoria L. (Frontiers in Public Health, 2023)
In June 2021, a condominium in Florida collapsed, with the loss of 98 lives. Search and rescue teams spent two weeks, recovering the victims. This study’s objective was to assess the presence of psychological symptoms that might emerge in the following months, using the PTSD Checklist for DSM-5 (PCL-5), Patient Health Questionnaire – 9 (PHQ-9), Generalized Anxiety Disorder – 7 (GAD-7), Suicide Cognitions Scale (SCS), and the Insomnia Severity Index (ISI). A monthly survey conducted for three months found that overall, mean scores on these measures did not indicate significant emotional distress. We then compared the scores when the group was divided into responders who recovered human remains and those who did not. Scores were significantly higher among the subgroup that recovered human remains. Fifty-three percent (53%) of this sub-group met the cut-off score for a provisional diagnosis of PTSD, depressive disorder or generalized anxiety disorder - 15% met the cut-off score criteria on the PCL-5 for probable PTSD, 36.8% for probable depressive disorder on the PHQ-9, and 26.3% for probable generalized anxiety disorder on the GAD-7. The results are consistent with other investigations examining mental health after mass disasters. Specifically, not all first responders will develop emotional distress, but certain recovery activities may put some responders at higher risk, with a percentage displaying a psychological distress. The results emphasize the need to assess the impact of these events on the mental health of first responders and to consider strategies to prevent or mitigate the development of impairing psychopathology.